2021
DOI: 10.31557/apjcc.2021.6.4.457-460
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Profile and Clinicopathological Correlates of Triple Negative Breast Cancer Patients at Regional Cancer Centre

Abstract: Background: Breast Cancer is the most common cancer among woman worldwide. In India breast cancer remains the leading cause of both incidence and mortality. Triple negative breast cancer is more difficult to treat as it does not respond to hormone therapy medicines or medicines that target receptor proteins (like HER 2 Neu). It is crucial for the physician to know the status of the disease as the patient can be subjected to a whole new avenue of treatment. The present study was done to assess the epidemiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…Lymphovascular infiltration is also associated with clinical characteristics as well as hormone receptor status. Similar studies were also seen in the study by Richa et al [44] in 2021 in India who received results from 249 samples studied, 198 (79,5%) of whom had negative LVI. Research by Sanges et al [24] in 2020 had the same result, namely negative LVI was the most common in 427 (55%) of the 1.009 TNBC patients studied.…”
Section: Discussionsupporting
confidence: 85%
“…Lymphovascular infiltration is also associated with clinical characteristics as well as hormone receptor status. Similar studies were also seen in the study by Richa et al [44] in 2021 in India who received results from 249 samples studied, 198 (79,5%) of whom had negative LVI. Research by Sanges et al [24] in 2020 had the same result, namely negative LVI was the most common in 427 (55%) of the 1.009 TNBC patients studied.…”
Section: Discussionsupporting
confidence: 85%
“… 4 In addition, other similar studies conducted yield similar results with mean age ranging from 45 to 52 years. 9 - 12 These scenarios of age characteristics of patients with breast cancer in these studies are consistent with the fact that an age of more than 40 years is a risk factor for the development of breast cancer. 13…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies of TNBC patients in US showed higher mean age at diagnosis, for example, 59.87±15.67 years (Tariq et al, 2014) and 59 years (Yeh et al, 2017). Meanwhile, three studies in South Asia showed lower mean age of TNBC patient with 46.26 ± 12.22 years in Pakistan (Sajid et al, 2014), 49 ± 12 years in Nepal (Khanal et al, 2020), and 46 ± 11.23 years in India (Verma et al, 2021). Clinical characteristics of TNBC were found to be influenced by the age of patients.…”
Section: Discussionmentioning
confidence: 92%
“…Clinicopathological parameters including age of patient, tumor stage, age at diagnosis, and status of patient during follow-up period, were obtained from the patients' medical records along with the informed consent from the patients. The cut-off value of age at diagnosis used in our statistical analysis is 40 years, as suggested by others (Khanal et al, 2020;Liedtke et al, 2013;Verma et al, 2021) Stromal TILs were evaluated from hematoxylin and eosin (H&E) stained slides and defined as percentage of lymphocytes over the analyzed stromal area. The evaluations were performed in five high power fields (400x magnification) and the counts were averaged.…”
Section: Methodsmentioning
confidence: 99%